Combination Of Goat Rumen And Mas Snails As Decomposer Bacteria In Manufacturing Empty Palm Bunch Compost - Fauzan Bintang Andaswara, Muhammad; Rusmini, Rusmini; Abidin, Zainal; Mudi, La; Daryono, Daryono; Anwar, Rusli; Arifin, Syaiful (International Journal of Science, Technology & Management, 2024)
One effort to utilize EPOFB waste is by composting EPOFB. Cellulose can be broken down by the activity of microorganisms that are capable of hydrolyzing cellulose as an energy source, such as bacteria and fungi. One solution for managing EFB waste is to utilize cellulose decomposing organisms, which come from goldfish snails (pomacea canaliculata) and goat rumen (caprovis spp.). The aim of this research is to calculate the length of time for composting, observe the physical properties of the compost and test the nutrient elements N, P, K, C/N ratio and pH, compost from EFB using decomposer bacteria from golden snails combined with goat rumen at the P1 level and the P2 level. using commercial bioactivators. Fertilizer results at each level were compared with the Indonesian National Standard SNI No./140/10/2004. This research was carried out at the Agronomy Laboratory of the Plantation Plant Cultivation Study Program and Pilot Gardens of the Samarinda State Agricultural Polytechnic, from June to September 2023. The research results show the length of time for composting to compost empty oil palm bunch waste at P1 level using a golden snail decomposer combined with rumen goats and P2 used a commercial biodecomposer for 53 days. Based on the results of research on the physical properties of empty oil palm fruit bunch waste compost at levels P1 and P2, the temperature at the end was the same, namely 28ºC, while the color, odor and texture parameters were better at level P2, namely blackish brown, odorless and slightly grainy in texture. The research results at the P2 treatment level were better in terms of the element parameters N, P, K and C, namely, N = 1.0343%, P = 0.2554% and K = 32.58, which met SNI 19-7030-2004 standards.